2021
DOI: 10.3390/ma14030614
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Properties and Applications of Si-Based Polymer-Derived Ceramics: A Review

Abstract: Ceramics derived from organic polymer precursors, which have exceptional mechanical and chemical properties that are stable up to temperatures slightly below 2000 °C, are referred to as polymer-derived ceramics (PDCs). These molecularly designed amorphous ceramics have the same high mechanical and chemical properties as conventional powder-based ceramics, but they also demonstrate improved oxidation resistance and creep resistance and low pyrolysis temperature. Since the early 1970s, PDCs have attracted widesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 94 publications
0
32
0
Order By: Relevance
“…1 Under appropriate synthesis conditions, PDCs such as silicon oxycarbide (SiOC), silicon oxycarbonitride (SiCN), and silicon carbide (SiC) can be synthesized via controlled pyrolysis of preceramic polymers such as polycarbosiloxanes, polycarbodiamides, and polycarbosilanes (see Figure 1). 2 PDCs are notable due to their high thermal stability, 3 as well as corrosion and creep resistance. They have potential use in mechanical and aerospace technologies 2,4 including manufacturing aircraft turbine engine components [5][6][7] and are proposed as anode materials in lithium ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…1 Under appropriate synthesis conditions, PDCs such as silicon oxycarbide (SiOC), silicon oxycarbonitride (SiCN), and silicon carbide (SiC) can be synthesized via controlled pyrolysis of preceramic polymers such as polycarbosiloxanes, polycarbodiamides, and polycarbosilanes (see Figure 1). 2 PDCs are notable due to their high thermal stability, 3 as well as corrosion and creep resistance. They have potential use in mechanical and aerospace technologies 2,4 including manufacturing aircraft turbine engine components [5][6][7] and are proposed as anode materials in lithium ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Materials with stable mechanical and chemical properties up to temperatures slightly below 2000 • C are known as PDCs. They are derived from organic polymer precursors [115]. Over the last decades, high-temperature structural ceramics have gained a reputation as structural materials for their low density, high oxidation and chemical resistance, excellent creep resistance, and thermal shock resistance.…”
Section: High Temperaturementioning
confidence: 99%
“…Ji et al investigated the antioxidation of amorphous SiBCN high-temperature fibers [115]. They reported that the SiBCN-based fibers are corroded at 1400 • C in the air and simulated combustion environments.…”
Section: High Temperaturementioning
confidence: 99%
“…4−6 A uniform polymer film on top of the porous substrate is ideal for the formation of high-quality ceramic membranes. 7−9 The dense polymer film deposition methods to date, typically, employ solvent-based techniques, such a slipcasting, 10 spin-coating, 11,12 and dip-coating, 13 which use potentially environmentally harmful solvents such as toluene, benzene, and tetrahydrofuran.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In comparison to their polymer counterparts, these membranes have been shown to be stable at high temperatures and pressures and can withstand the corrosive environments that are involved in hydrogen production. Such inorganic membranes are often fabricated by the application of a preceramic silicon-containing polymer film on a mechanically strong porous ceramic substrate and its subsequent pyrolysis. A uniform polymer film on top of the porous substrate is ideal for the formation of high-quality ceramic membranes. The dense polymer film deposition methods to date, typically, employ solvent-based techniques, such a slip-casting, spin-coating, , and dip-coating, which use potentially environmentally harmful solvents such as toluene, benzene, and tetrahydrofuran.…”
Section: Introductionmentioning
confidence: 99%